Negative active material for suppressing zinc dendrite and method for manufacturing same, negative material for zinc-nickel battery, and negative electrode

CN117438548BActive Publication Date: 2026-10-30SHANDONG HETAI NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210853768.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-12
Publication Date
2026-10-30
Estimated Expiration
2042-07-12

AI Technical Summary

Technical Problem

随着电池循环的进行,锌枝晶生长更为严重,甚至出现短路的现象,电池充放电容量急剧降低,循环性能严重下降

Benefits of technology

[0020](1)本发明对锌电极材料进行改性,所用负极活性物质为硫掺杂碳包覆氧化锌,其具有抑制锌枝晶生长的作用,由于硫和碳对锌元素都具备吸附能力,可以起到抑制偏锌酸根离子溶出的作用,由此可以减少锌镍电池充放过程中电容量的下降,提高电池循环性能;同时,硫掺杂碳可有效改善碳包覆氧化锌的电解液侵润性,有利于提高电极内氢氧根离子传导,有助于实现锌镍电池大电流充放电。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003740949060000011
    Figure HDA0003740949060000011
  • Figure HDA0003740949060000012
    Figure HDA0003740949060000012
  • Figure HDA0003740949060000013
    Figure HDA0003740949060000013
Patent Text Reader

Abstract

The application relates to the technical field of batteries, and provides a negative electrode active material for inhibiting zinc dendrites, a preparation method thereof, a zinc-nickel battery negative electrode material and a negative electrode. The negative electrode active material is sulfur-doped carbon-coated zinc oxide, and raw materials of the sulfur-doped carbon-coated zinc oxide include zinc oxide, a carbon source, a sulfur-containing organic compound and deionized water. The zinc electrode material is modified, the negative electrode active material is sulfur-doped carbon-coated zinc oxide, the sulfur-doped carbon-coated zinc oxide has the effect of inhibiting the growth of zinc dendrites, sulfur and carbon have the adsorption capacity for zinc elements, can inhibit the dissolution of the zincate ion, can reduce the decrease of the electric capacity in the charging and discharging process of the zinc-nickel battery, and can improve the cycle performance of the battery. Meanwhile, the sulfur-doped carbon can effectively improve the electrolyte wettability of the carbon-coated zinc oxide, is beneficial to improving the conduction of the hydroxyl ion in the electrode, and is helpful to realizing the large-current charging and discharging of the zinc-nickel battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a negative electrode active material for suppressing zinc dendrites and its preparation method, a zinc-nickel battery negative electrode material, and a negative electrode. Background Technology

[0002] Zinc-nickel batteries boast advantages such as high safety, non-flammability and non-explosion, environmental friendliness and economy, and high specific energy density, making them one of the most popular batteries in the current new energy industry. Compared with existing rechargeable alkaline batteries, zinc-nickel batteries can achieve a specific energy density of 80-120 Wh / kg, far exceeding lead-acid and nickel-cadmium batteries. Furthermore, zinc-nickel batteries are non-toxic and pollution-free, offering significant advantages over existing nickel-cadmium batteries; and compared to existing lithium-ion batteries, they offer higher safety, being non-flammable and non-explosive, allowing for use in fields with higher safety requirements. Moreover, zinc, as the main material of the battery's negative electrode, is inexpensive, reducing manufacturing costs. Finally, zinc-nickel batteries exhibit superior high-rate performance, allowing for high-current charging and discharging, and good low-temperature performance, making them one of the most promising batteries in the power battery field.

[0003] However, existing zinc-nickel batteries suffer from a significant zinc dendrite problem: zinc dendrites grow on the surface of the zinc negative electrode, piercing the separator and reaching the positive electrode, causing a short circuit. Additionally, the zinc electrode may dissolve and deform. These issues are primarily attributed to defects in the zinc electrode itself. During discharge, the zinc electrode generates zinc oxide and zinc hydroxide, and since the electrolyte in zinc-nickel batteries is strongly alkaline, these substances dissolve in the electrolyte. As the battery cycles, zinc dendrite growth becomes more severe, even leading to short circuits, a sharp decrease in charge / discharge capacity, and a significant decline in cycle performance. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is how to suppress the growth of zinc dendrites and electrode dissolution, thereby improving the battery cycle performance.

[0005] To solve the above-mentioned technical problems, the first aspect of the present invention provides a negative electrode active material for suppressing zinc dendrites, wherein the negative electrode active material is sulfur-doped carbon-coated zinc oxide, and the raw materials for the sulfur-doped carbon-coated zinc oxide include zinc oxide, carbon source, sulfur-containing organic compound and deionized water.

[0006] Furthermore, the mass ratio of the raw materials for the sulfur-doped carbon-coated zinc oxide is zinc oxide: carbon source: sulfur-containing organic compound: deionized water = 1:(0.1-0.5):(0.05-0.5):(0.5-2). When the mass ratio of each material is within this range, a sulfur-doped carbon coating layer can be effectively formed on the surface of zinc oxide.

[0007] Furthermore, the carbon source is selected from one or more of the following: glucose, sucrose, fructose, and starch. The carbon source is a water-soluble aldehyde compound that provides carbon to form a carbon-coated structure on the zinc oxide surface.

[0008] Furthermore, the sulfur-containing organic compound material is selected from one or more of the following: thiourea, L-cysteine, L-histidine, thioglycolic acid, and methionine. The sulfur-containing organic compound is a soluble sulfide that can be effectively dispersed in aqueous solution, and it is used to provide the sulfur element required for doping.

[0009] A second aspect of the present invention provides a method for preparing the above-mentioned negative electrode active material for inhibiting zinc dendrites, comprising the following steps:

[0010] S1. Add grinding media to a ball mill, weigh out carbon source, sulfur-containing organic matter and deionized water, add them to the ball mill and mix them to form a water-soluble prepolymer;

[0011] S2. Weigh zinc oxide and add it to the water-soluble prepolymer, then continue ball milling to form a slurry;

[0012] S3. The slurry is placed in a spray dryer for spray drying to obtain dried raw material powder;

[0013] S4. Place the raw material powder in a calcining furnace, heat it to a set temperature under inert gas protection, keep it heated and calcined, and cool it to room temperature to obtain sulfur-doped carbon-coated zinc oxide.

[0014] Furthermore, in step S4, the calcination temperature is 700-1000℃, and the holding time is 2-6h.

[0015] Furthermore, the grinding media in step S1 includes zirconia balls of five different sizes, with a mass ratio of 10mm diameter zirconia balls : 5mm diameter zirconia balls : 2mm diameter zirconia balls : 1mm diameter zirconia balls : 0.5mm diameter zirconia balls = 1 : (1-2) : (1-3) : (3-7) : (0.5-10). Zirconia balls have the advantages of high strength, high toughness, good wear resistance, high temperature resistance, and corrosion resistance. They also cause minimal dispersion and contamination of the grinding material. Mixing zirconia balls according to a certain diameter-to-weight ratio allows the particle size of the material to be controlled within the required range.

[0016] Furthermore, in steps S1 and S2, the ball mill rotation speed is 5-50 rad / min, and the ball milling time is 15-60 min. In step S3, the feed temperature of the slurry entering the spray dryer is 160-300℃, the discharge temperature is 60-150℃, the feed rate is 1-5 L / h, and the centrifugal disc rotation speed of the spray dryer is 3000-5000 rad / min. The spray dryer is a device that can simultaneously complete drying and granulation. All its products are spherical particles. It has a fast drying speed, and the surface area of ​​the liquid material is greatly increased after atomization. By controlling the feed temperature, discharge temperature, and feed rate of the slurry entering the spray dryer, raw material powder with uniform particle size, good flowability, good solubility, high product purity, and good quality can be obtained.

[0017] A third aspect of the present invention provides a zinc-nickel battery anode material comprising the above-mentioned anode active material for inhibiting zinc dendrites.

[0018] A fourth aspect of the present invention provides a zinc-nickel battery negative electrode, comprising a current collector and the aforementioned negative electrode material, wherein the negative electrode material is coated on the current collector.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention modifies the zinc electrode material. The negative electrode active material used is sulfur-doped carbon-coated zinc oxide, which has the effect of inhibiting the growth of zinc dendrites. Since sulfur and carbon have the ability to adsorb zinc elements, they can inhibit the dissolution of zincate ions, thereby reducing the decrease in capacitance during the charging and discharging of zinc-nickel batteries and improving the cycle performance of batteries. At the same time, sulfur-doped carbon can effectively improve the electrolyte wettability of carbon-coated zinc oxide, which is conducive to improving the conduction of hydroxide ions in the electrode and helps to realize high-current charging and discharging of zinc-nickel batteries.

[0021] (2) The sulfur doped in the negative electrode active material of the present invention will also coordinate with the sulfur-loving negative electrode active material elements such as Sn, Sb and Bi in the electrolyte to form a metal coordination polymer, which optimizes the composition, structure and thickness of the carbon coating layer, thereby improving the specific capacity of the negative electrode material, increasing the hydrogen escape potential of the negative electrode material, and further improving the charge and discharge efficiency of the zinc-nickel battery.

[0022] (3) The method for preparing the negative electrode active material of the present invention uses a ball mill to ball mill the raw materials so that the raw materials can be fully mixed. By controlling the speed and time of the ball mill, the viscosity of the material can be adjusted to make it more suitable for the feeding process of the spray dryer. Moreover, five different sizes of zirconia balls are added to the ball mill as grinding media. The material after ball milling has high uniformity, more uniform particle size, and larger specific surface area, so that the sulfur-doped carbon coating layer can be more uniformly covered on the surface of zinc oxide particles during the spray drying process.

[0023] (4) The method for preparing the negative electrode active material of the present invention involves dissolving and prepolymerizing a sulfur-containing organic compound and a carbon source in water, and prepolymerizing the sulfur-containing compound and an aldehyde compound (such as monosaccharides, polysaccharides, etc.) to obtain a water-soluble thiourea-formaldehyde prepolymer. The affinity between sulfur in the thiourea-formaldehyde resin and zinc oxide helps to disperse the thiourea-formaldehyde resin and zinc oxide evenly. After spray drying, a uniform resin modification layer is obtained covering the surface of the nano zinc oxide particles. In the subsequent calcination process, the urea-formaldehyde prepolymer undergoes deep polymerization and carbonization to obtain a functionalized carbon coating layer. The sulfur doping in the carbon layer will also increase the hydrogen escape overpotential and improve the charge and discharge efficiency of the battery. Attached Figure Description

[0024] Figure 1 A process flow diagram for preparing the negative electrode active material provided for embodiments of the present invention;

[0025] Figure 2 The XRD diffraction pattern of the negative electrode active material prepared in Example 1 of this invention;

[0026] Figure 3 This is a scanning electron microscope image of zinc oxide.

[0027] Figure 4 This is a scanning electron microscope image of sulfur-doped carbon-coated zinc oxide prepared in Example 1 of the present invention;

[0028] Figure 5 This is a scanning electron microscope image of sulfur-doped carbon-coated zinc oxide prepared in Example 1 of the present invention;

[0029] Figure 6 This is a scanning electron microscope image of sulfur-doped carbon-coated zinc oxide prepared in Example 2 of the present invention. Detailed Implementation

[0030] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be noted that the following embodiments are only used to illustrate the implementation methods and typical parameters of the present invention, and are not intended to limit the parameter range described in the present invention. Reasonable variations derived therefrom are still within the protection scope of the claims of the present invention.

[0031] It should be noted that the endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0032] A specific embodiment of the present invention provides a zinc-nickel battery negative electrode, which includes a current collector and a negative electrode material coated on the current collector. The negative electrode material includes a negative electrode active material that inhibits zinc dendrite formation, and may further include additives, conductive agents, binders, dispersants, etc. The negative electrode active material is sulfur-doped carbon-coated zinc oxide, prepared by reacting zinc oxide, a carbon source, a sulfur-containing organic compound, and deionized water.

[0033] In a specific implementation, the mass ratio of the raw materials for the negative electrode active material is zinc oxide: carbon source: sulfur-containing organic compound: deionized water = 1:(0.1-0.5):(0.05-0.5):(0.5-2). The carbon source is a water-soluble aldehyde compound, such as glucose, sucrose, fructose, starch, etc.; the sulfur-containing compound is a water-soluble compound such as thiourea, L-cysteine, L-histidine, thioglycolic acid, methionine, etc.

[0034] The preparation method of the above-mentioned negative electrode active material is as follows: Figure 1 As shown, it includes the following steps:

[0035] S1. Grinding media are added to a ball mill. A carbon source, sulfur-containing organic compound, and deionized water are weighed and added to the ball mill for ball milling and mixing to form a water-soluble prepolymer. The sulfur-containing organic compound and carbon source are first dissolved and prepolymerized in water. The sulfur-containing compound and aldehyde compound are then prepolymerized to obtain a water-soluble thiourea-formaldehyde prepolymer. The affinity of sulfur in the thiourea-formaldehyde resin for zinc oxide helps to ensure uniform dispersion of the thiourea-formaldehyde resin and zinc oxide.

[0036] S2. Weigh zinc oxide and add it to the water-soluble prepolymer obtained in step S1, then continue ball milling to form a slurry. In steps S1 and S2, the ball mill speed is 5-50 rad / min, and the milling time is 15-60 min. The slurry viscosity can be adjusted by controlling the ball mill speed and time to make it more suitable for feeding into the spray dryer. Five different sizes of zirconia balls are added to the ball mill as grinding media. The mass ratio of each size of zirconia ball is 10mm diameter : 5mm diameter : 2mm diameter : 1mm diameter : 0.5mm diameter = 1 : (1-2) : (1-3) : (3-7) : (0.5-10). The material after ball milling has high uniformity, more uniform particle size, and a larger specific surface area.

[0037] S3. The slurry obtained in step S2 is placed into a spray dryer for spray drying. The feed temperature is 160-300℃, the discharge temperature is 60-150℃, the feed rate is 1-5 L / h, and the centrifugal disc rotation speed of the spray dryer is 3000-5000 rad / min, resulting in dried raw material powder. During the spray drying process, a sulfur-doped carbon coating layer is uniformly applied to the surface of the zinc oxide particles. The feed rate and centrifugal disc rotation speed are matched to control the discharge rate and particle size of the material, preventing clogging of the spray dryer.

[0038] S4. Place the raw material powder obtained in step S3 into a calcination furnace. Inert gas is introduced at a temperature below 100°C. After confirming that the oxygen content in the furnace is ≤100ppm, the temperature is increased. The inert gas used is a mixture of one or two of nitrogen and argon. Under the protection of the inert gas, the temperature is increased to the set temperature, and then calcined at 700-1000°C for 2-6 hours. After cooling to room temperature, sulfur-doped carbon-coated zinc oxide is obtained. During the calcination process, deep polymerization and carbonization of urea-formaldehyde prepolymer occur, resulting in a functionalized carbon coating layer. The sulfur doping in the carbon layer also increases the hydrogen escape overpotential, improving the charge and discharge efficiency.

[0039] Sulfur-doped carbon-coated zinc oxide inhibits zinc dendrite growth. Since both sulfur and carbon adsorb zinc, they suppress the dissolution of zincate ions, thus reducing the capacity drop during charge-discharge cycles and improving battery cycle performance. Sulfur-doped carbon effectively improves the electrolyte wettability of carbon-coated zinc oxide, enhancing hydroxide ion conduction within the electrode and facilitating high-current charge-discharge in zinc-nickel batteries. Furthermore, the doped sulfur coordinates with thiophilic anode active materials such as Sn, Sb, and Bi in the electrolyte to form metal coordination polymers, optimizing the composition, structure, and thickness of the carbon coating layer. This improves the specific capacity and hydrogen escape potential of the anode material, further enhancing the charge-discharge efficiency of the zinc-nickel battery.

[0040] The present invention will be described in detail below through specific embodiments.

[0041] Example 1

[0042] The preparation of sulfur-doped carbon-coated zinc oxide as a negative electrode active material includes the following steps:

[0043] Add zirconia balls as grinding media to a ball mill. The mass ratio of zirconia balls of different sizes is 10mm diameter: 5mm diameter: 2mm diameter: 1mm diameter: 0.5mm diameter = 1:2:2:4.5:0.5. Weigh 0.5kg of glucose, 0.1kg of thiourea, and 1kg of deionized water and add them to the ball mill. Set the ball mill speed to 25 rad / min and the ball milling time to 30min. After ball milling and mixing, a water-soluble prepolymer is formed.

[0044] Add 1 kg of zinc oxide to the water-soluble prepolymer, set the ball mill speed to 50 rad / min, and the ball milling time to 45 min to form a slurry.

[0045] The obtained slurry was placed into a spray dryer for spray drying. The feed rate of the spray dryer was set to 1L / h, the feed temperature was set to 150℃, the discharge temperature was set to 90℃, and the centrifugal disc speed was set to 3000rad / min. After spray drying, the dried raw material powder was obtained.

[0046] The obtained dry raw material powder is placed in a calcining furnace and heated to 800°C under nitrogen protection. It is then kept at this temperature for 4 hours. After the temperature inside the furnace cools down to room temperature, the material taken out is sulfur-doped carbon-coated zinc oxide.

[0047] XRD diffraction analysis was performed on the sulfur-doped carbon-coated zinc oxide obtained in this embodiment, and the results are as follows: Figure 2 As shown in the figure, the carbon-doped zinc oxide has the same crystal structure as the untreated zinc oxide, indicating that the crystal structure of zinc oxide was not destroyed by the above preparation method; no diffraction peaks of carbon and sulfur were found in the XRD diffraction pattern, indicating that the carbon layer and the doped sulfur exist in the amorphous or microcrystalline thin layer structure.

[0048] The scanning electron microscope (SEM) image of sulfur-doped carbon-coated zinc oxide obtained in this embodiment is shown below. Figure 4 As shown, with Figure 3 Compared to undoped and uncoated zinc oxide, it is evident that the interface of the zinc oxide particles becomes blurred after coating. The zinc oxide particles are connected together by the coating layer. This sulfur-doped carbon coating layer effectively improves the wettability of the zinc oxide electrolyte, which is beneficial for improving the conduction of hydroxide ions within the electrode and facilitates high-current charging and discharging of zinc-nickel batteries. Figure 5 The transmission electron microscope image shown more clearly illustrates that a transparent doped layer is coated on the surface of the black zinc oxide particles.

[0049] Example 2

[0050] The preparation of sulfur-doped carbon-coated zinc oxide as a negative electrode active material includes the following steps:

[0051] Add zirconia balls as grinding media to a ball mill. The mass ratio of zirconia balls of different sizes is 10mm diameter: 5mm diameter: 2mm diameter: 1mm diameter: 0.5mm diameter = 1:2:2:3:2. Weigh 0.4kg of glucose, 0.08kg of thiourea, and 0.8kg of deionized water and add them to the ball mill. Set the ball mill speed to 50 rad / min and the ball milling time to 60min. After ball milling and mixing, a water-soluble prepolymer is formed.

[0052] Add 1 kg of zinc oxide to the water-soluble prepolymer, set the ball mill speed to 30 rad / min, and the ball milling time to 30 min to form a slurry.

[0053] The obtained slurry was placed into a spray dryer for spray drying. The feed rate of the spray dryer was set to 1L / h, the feed temperature was set to 180℃, the discharge temperature was set to 100℃, and the centrifugal disc speed was set to 3500rad / min. After spray drying, the dried raw material powder was obtained.

[0054] The obtained dry raw material powder is placed in a calcining furnace and heated to 1000℃ under argon protection. It is then kept at this temperature for 3 hours. After the temperature inside the furnace cools down to room temperature, the material taken out is sulfur-doped carbon-coated zinc oxide.

[0055] The scanning electron microscope (SEM) image of sulfur-doped carbon-coated zinc oxide obtained in this embodiment is shown below. Figure 6 As shown, with Figure 3 Compared to zinc oxide without doping and coating, it is obvious that the interface of zinc oxide particles becomes blurred after being coated, and the zinc oxide particles are connected together by the coating layer.

[0056] Example 3

[0057] The preparation of sulfur-doped carbon-coated zinc oxide as a negative electrode active material includes the following steps:

[0058] Add zirconia balls as grinding media to a ball mill. The mass ratio of zirconia balls of different sizes is 1:2:3:4:6 (10mm diameter zirconia balls : 5mm diameter zirconia balls : 2mm diameter zirconia balls : 1mm diameter zirconia balls : 0.5mm diameter zirconia balls). Weigh 0.1kg of sucrose, 0.1kg of L-cysteine, and 0.6kg of deionized water and add them to the ball mill. Set the ball mill speed to 10 rad / min and the ball milling time to 40min. After ball milling and mixing, a water-soluble prepolymer is formed.

[0059] Add 1 kg of zinc oxide to the water-soluble prepolymer, set the ball mill speed to 20 rad / min, and the ball milling time to 50 min to form a slurry.

[0060] The obtained slurry was placed into a spray dryer for spray drying. The feed rate of the spray dryer was set to 3L / h, the feed temperature was set to 300℃, the discharge temperature was set to 150℃, and the centrifugal disc speed was set to 4000rad / min. After spray drying, the dried raw material powder was obtained.

[0061] The obtained dry raw material powder is placed in a calcining furnace and heated to 700°C under nitrogen protection. It is then kept at this temperature for 6 hours. After the temperature inside the furnace cools down to room temperature, the material taken out is sulfur-doped carbon-coated zinc oxide.

[0062] Example 4

[0063] The preparation of sulfur-doped carbon-coated zinc oxide as a negative electrode active material includes the following steps:

[0064] Add zirconia balls as grinding media to a ball mill. The mass ratio of zirconia balls of different sizes is 1:1.5:2:5:10 (10mm diameter zirconia balls : 5mm diameter zirconia balls : 2mm diameter zirconia balls : 1mm diameter zirconia balls : 0.5mm diameter zirconia balls). Weigh 0.4kg of fructose, 0.05kg of L-histidine, and 0.5kg of deionized water and add them to the ball mill. Set the ball mill speed to 5 rad / min and the ball milling time to 60min. After ball milling and mixing, a water-soluble prepolymer is formed.

[0065] Add 1 kg of zinc oxide to the water-soluble prepolymer, set the ball mill speed to 30 rad / min, and the ball milling time to 20 min to form a slurry.

[0066] The obtained slurry was placed into a spray dryer for spray drying. The feed rate of the spray dryer was set to 4 L / h, the feed temperature was set to 250℃, the discharge temperature was set to 120℃, and the centrifugal disc speed was set to 4500 rad / min. After spray drying, the dried raw material powder was obtained.

[0067] The obtained dry raw material powder is placed in a calcining furnace and heated to 900°C under argon protection. It is then kept at this temperature for 3 hours. After the temperature inside the furnace cools down to room temperature, the material taken out is sulfur-doped carbon-coated zinc oxide.

[0068] Example 5

[0069] The preparation of sulfur-doped carbon-coated zinc oxide as a negative electrode active material includes the following steps:

[0070] Add zirconia balls as grinding media to a ball mill. The mass ratio of zirconia balls of different sizes is 1:1.6:2.5:5.5:8 ​​(10mm diameter zirconia balls : 5mm diameter zirconia balls : 2mm diameter zirconia balls : 1mm diameter zirconia balls : 0.5mm diameter zirconia balls). Weigh 0.35kg of starch, 0.35kg of thioglycolic acid, and 1.6kg of deionized water and add them to the ball mill. Set the ball mill speed to 45 rad / min and the ball milling time to 25min. After ball milling and mixing, a water-soluble prepolymer is formed.

[0071] Add 1 kg of zinc oxide to the water-soluble prepolymer, set the ball mill speed to 35 rad / min, and the ball milling time to 35 min to form a slurry.

[0072] The obtained slurry was placed into a spray dryer for spray drying. The feed rate of the spray dryer was set to 3.5 L / h, the feed temperature was set to 260℃, the discharge temperature was set to 80℃, and the centrifugal disc speed was set to 3300 rad / min. After spray drying, the dried raw material powder was obtained.

[0073] The obtained dry raw material powder is placed in a calcining furnace and heated to 750°C under nitrogen protection. It is then kept at this temperature for 2.5 hours. After the temperature inside the furnace cools down to room temperature, the material taken out is sulfur-doped carbon-coated zinc oxide.

[0074] Example 6

[0075] The preparation of sulfur-doped carbon-coated zinc oxide as a negative electrode active material includes the following steps:

[0076] Add zirconia balls as grinding media to a ball mill. The mass ratio of zirconia balls of different sizes is 10mm diameter: 5mm diameter: 2mm diameter: 1mm diameter: 0.5mm diameter = 1:1:1:4:7. Weigh out 0.5kg of fructose, 0.5kg of methionine, and 2kg of deionized water, and add them to the ball mill. Set the ball mill speed to 50 rad / min and the ball milling time to 60min. After ball milling and mixing, a water-soluble prepolymer is formed.

[0077] Add 1 kg of zinc oxide to the water-soluble prepolymer, set the ball mill speed to 50 rad / min, and the ball milling time to 60 min to form a slurry.

[0078] The obtained slurry was placed into a spray dryer for spray drying. The feed rate of the spray dryer was set to 5 L / h, the feed temperature was set to 280℃, the discharge temperature was set to 75℃, and the centrifugal disc speed was set to 5000 rad / min. After spray drying, the dried raw material powder was obtained.

[0079] The obtained dry raw material powder is placed in a calcining furnace and heated to 950°C under nitrogen protection. It is then kept at this temperature for 5.5 hours. After the temperature inside the furnace cools down to room temperature, the material taken out is sulfur-doped carbon-coated zinc oxide.

[0080] Comparative Example

[0081] Zinc oxide, carbon-coated zinc oxide, and sulfur-doped carbon-coated zinc oxide (as in Example 1) were used as negative electrode active materials. 600g of the negative electrode active material, 200g of calcium carbonate additive, 30g of graphite conductive agent, 100g of 60% PTFE emulsion binder, and 200g of deionized water dispersant were weighed and mixed uniformly to form a negative electrode slurry. This slurry was then coated onto the surface of the current collector to form the negative electrode, resulting in a 1.6V / 8Ah single-cell battery. Battery capacity tests were performed on the three types of batteries.

[0082] A single-cell battery made using zinc oxide as the negative electrode active material exhibited rapid capacity decay during capacity testing, reaching near zero after 50 cycles. Single-cell batteries made using carbon-coated zinc oxide and sulfur-doped carbon-coated zinc oxide as the negative electrode active material showed relatively stable discharge capacities for the first 400 cycles, indicating good battery consistency. However, as the cycling test continued, at 800 cycles, the discharge capacity of the carbon-coated zinc oxide cell decreased from 8 Ah to 5 Ah, representing 62.5% of its original capacity. Conversely, at 800 cycles, the sulfur-doped carbon-coated zinc oxide cell decreased from 8 Ah to 6.4 Ah, still retaining 80% of its original capacity. Therefore, the capacity decay rate of the carbon-coated zinc oxide cell was significantly faster than that of the sulfur-doped carbon-coated zinc oxide cell.

[0083] The above results indicate that the sulfur-doped carbon-coated zinc oxide of the present invention, as the negative electrode active material, can effectively suppress the growth of zinc dendrites, and the cycle life of the single cell battery made with the sulfur-doped carbon-coated zinc oxide of the present invention as the negative electrode active material is greatly improved.

[0084] While the present invention has been disclosed above, it is not limited thereto. Any person skilled in the art can make various modifications and alterations without departing from the spirit and scope of the invention; therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.

Claims

1. A negative electrode active material for inhibiting zinc dendrite formation, characterized in that, The negative electrode active material is sulfur-doped carbon-coated zinc oxide. The raw materials for sulfur-doped carbon-coated zinc oxide include zinc oxide, carbon source, sulfur-containing organic compound and deionized water. The mass ratio of the raw materials for sulfur-doped carbon-coated zinc oxide is zinc oxide: carbon source: sulfur-containing organic compound: deionized water = 1:(0.1-0.5):(0.05-0.5):(0.5-2). The carbon source is glucose and the sulfur-containing organic compound is thiourea. The preparation method of the negative electrode active material includes the following steps: S1. Add grinding media to a ball mill, weigh out carbon source, sulfur-containing organic matter and deionized water, add them to the ball mill and mix them to form a water-soluble prepolymer; S2. Weigh zinc oxide and add it to the water-soluble prepolymer, then continue ball milling to form a slurry; S3. The slurry is placed in a spray dryer for spray drying to obtain dried raw material powder; S4. Place the raw material powder in a calcining furnace, heat it to a set temperature under inert gas protection, keep it heated and calcined, and cool it to room temperature to obtain sulfur-doped carbon-coated zinc oxide.

2. A method for preparing the negative electrode active material for inhibiting zinc dendrites as described in claim 1, characterized in that, Includes the following steps: S1. Add grinding media to a ball mill, weigh out carbon source, sulfur-containing organic matter and deionized water, add them to the ball mill and mix them to form a water-soluble prepolymer; S2. Weigh zinc oxide and add it to the water-soluble prepolymer, then continue ball milling to form a slurry; S3. The slurry is placed in a spray dryer for spray drying to obtain dried raw material powder; S4. Place the raw material powder in a calcining furnace, heat it to a set temperature under inert gas protection, keep it heated and calcined, and cool it to room temperature to obtain sulfur-doped carbon-coated zinc oxide.

3. The method for preparing the negative electrode active material for inhibiting zinc dendrites according to claim 2, characterized in that, In step S4, the roasting temperature is 700-1000℃ and the holding time is 2-6h.

4. The method for preparing the negative electrode active material for inhibiting zinc dendrites according to claim 2, characterized in that, The grinding media in step S1 includes zirconia balls of five different sizes, with the mass ratio of each size being 10mm diameter zirconia balls : 5mm diameter zirconia balls : 2mm diameter zirconia balls : 1mm diameter zirconia balls : 0.5mm diameter zirconia balls = 1 : (1-2) : (1-3) : (3-7) : (0.5-10).

5. The method for preparing the negative electrode active material for inhibiting zinc dendrites according to claim 2, characterized in that, In steps S1 and S2, the ball mill speed is 5-50 rad / min, the ball milling time is 15-60 min, the slurry entering the spray dryer in step S3 has a feed temperature of 160-300℃, an outlet temperature of 60-150℃, a feed rate of 1-5 L / h, and a centrifugal disc speed of 3000-5000 rad / min.

6. A zinc-nickel battery anode material, characterized in that, Includes the negative electrode active material for inhibiting zinc dendrites as described in claim 1.

7. A zinc-nickel battery negative electrode, characterized in that, It includes a current collector and a negative electrode material as described in claim 6, wherein the negative electrode material is coated on the current collector.

Citation Information

Patent Citations

  • Preparation method of doped lithium ion battery positive electrode material

    CN111490251A

  • Negative electrode material and preparation method thereof, battery and terminal

    CN112838197A